Analysis of coupled lateral-torsional-pounding responses of adjacent asymmetric structures to seismic motion - Gong, Lei. (2008)
The main objective of this research is to study seismic induced coupled lateral-torsional responses of assymmetric structures and coupled torsional-pounding responses of two adjacent asymmetric or symmetric structures.